Correlation between X-Ray diffraction pattern and microstructure of surface of E690 high-strength steel induced by laser-shock processing. (January 2022) - Cao, Yupeng; Zhu, Pengfei; Shi, Weidong; Hua, Guoran; Wang, Heng; Qiu, Ming
Abstract: To examine the relationship between the X-ray Diffraction (XRD) pattern and microstructure of the surface of E690 high-strength steel induced by laser shocks, X-ray diffractometry and transmission electron microscopy (TEM) were used to detect the laser-impact zone on the steel surface to obtain its diffraction pattern and microstructural morphology, followed by the establishment of a surface microstructure response model of the E690 high-strength steel under laser shock. The grain size of the impacted surface decreased with an increase in laser power density (LPD). When the LPD reached 4.07 GW/cm 2, Ostwald ripening was observed in the TEM images and the grain size increased during the later stages of spinodal decomposition. When the LPD was 5.09 GW/cm 2, nanograins were detected on the surface of the laser-impacted area. The X-ray diffraction result on the surface of the E690 high-strength steel was consistent with the microstructural analysis using TEM, which proves that the microstructural response of E690 high-strength steel under laser shock can be described by the surface microstructure response model. Highlights: Grain size increased abnormally at 4.07 GW/cm 2 with Ostwald ripening effect observed. The grain size calculated by XRD was correlated with that observed by TEM. Nanocrystals were observed at 5.09 GW/cm 2 . In general, the grain size decreased with an increase in laser power density.